STUDI PENGGUNAAN BATU TANGKILING UNTUK KONSTRUKSI PERKERASAN HRS-WC DI PALANGKA RAYA - Erwin Ratna Wati (Jurnal Teknologi Berkelanjutan, 2015)
Katingan is one of the regencies in Central Kalimantan province, which has deposits of mountain stone and quarried sand in Bukit Tangkiling. Problem in the area is that it is hard to obtain aggregate fraction proportions that pass No. 30 (0.60 mm) sieve as required in the specification of gap graded range, so if the gap graded could not be met, then semi-gap graded is used.HRS is also called gap-graded pavement, which has more fine aggregate than coarse aggregate compared to asphalt concrete, and resulted in flexible pavement that can be passed by vehicles comfortably. HRS-WC mixture relies on the bond between the bonding agents, coarse aggregate, fine aggregate, and filler, unlike asphalt concrete, which relies on coarse aggregate interlocking. HRS-WC utilizes gap gradation and provides good flexibility since the usage of gap gradation gives a high VMA value because more cavities are filled with asphalt. A higher VMA value results in thicker concrete blanket and creates flexible pavement that is comfortably passed by vehicles.Testing standards utilized in this research are Standar Nasional Indonesia (SNI) and American Association of State Highway and Transportation Official (AASHTO). Methods implemented in this research are to identify the characteristics of asphalt mixture that meets the specification.Based on the result of Marshall standard testing in COA 7.3% with gap level of 5%, density value is 2.248 g/cm3, VMA value is 20.40%, VIM is 4.3%, VBM value is 79.45%, stability value is 1375 kg, flow falue is 3.45%, and MQ value is 450 kg/cm. The research shows that the gap level of 5%, 10%, 15% and 20% has high density, VMA, VFB, and flow value, but low stability, VIM, and MQ value. This result shows that there is a strong correlation between Marshall’s characteristic with the gap gradation level. The best gradation variation is variation 1, which is the gradation that has gap level of 5%. Since this variation gives higher value of density, VMA, VFB, and flow, it results in flexible and comfortable pavement.